INTEGRASI KURIKULUM PESANTREN DAN MADRASAH (STUDI KASUS DI PONDOK PESANTREN AL-ISHLAH JENGGAWAH JEMBER) - Mohammad Shohibul Anwar; Miftahul Huda; Rodiatul Maghfiroh (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
At the beginning of the establhisment of the Al –Ishlah Jenggawah Islamic boarding school, it only focused on learning Islamic treasures such as reciting the traditional book and so on which aimed to scholars ora kyai. With the current developments, Islamic boarding schools must adjust by integrating the learning currulum with madrasah. so that in the current era, graduates of the Al-Ishlah Islamic boarding school can study at universities or work in government or private institutions. The research used is a descriptive qualitative approach and data collection by observation, interviews, and documentation. After the data is obtained, it is reduced, and final conclusion is presented. The Conclusion of this study are first, the concept of integration of the Al-Ishlah Jenggawah Islamic Boarding School curriculum is a combination or combination of cottage and madrasah materials simultaneously, continuously, Second, the integration of the Al –Ishlah Jenggawah Islamic Boarding School curriculum integration is carried ot as follws : 1) integration cottage of material in the form the of the nahwu sobah subject into madrasah material, 2) Application in the use of foreign language (Arabic and English) in daily activites, 3) Compulsory programs learning 6 years and 4 years, 4) Integration of Islamic boarding school materials, namely classic/yellow books into the madrasah subject schedule, 5) Application of the language of instruction in learning in foreign language class. Keywords: Integration, Curriculum, Islamic boarding school, madrasah.